Spiritual Holy Water Sites in Ethiopia: Unrecognized High-Risk Settings for Transmission of Pulmonary Tuberculosis - Melese Abate Reta; Nontuthuko Excellent Maningi; Gizachew Yismaw Wubetu; Steve A. S. Olorunju; P. Bernard Fourie (International Journal of Microbiology)
Ethiopia is a high-tuberculosis (TB) burden country with 157 new cases per 100,000 people, with 23,800 TB-related deaths in 2020. In Ethiopia, TB patients have different healthcare-seeking behaviors. They frequently visit spiritual places, such as holy water sites (HWSs), to seek treatment for their illness spiritually. This study examined the prevalence of pulmonary TB (PTB) and drug susceptibility profiles of Mycobacterium tuberculosis (MTB) isolates among spiritual HWS attendees in Northwest Ethiopia. A cross-sectional study was conducted from June 2019 to March 2020. Sputum samples were collected, processed, and cultured using Löwenstein–Jensen (LJ) culture medium. Second-generation line probe assays (LPAs), GenoType®MTBDRplus VER2.0 and GenoType®MTBDRsl VER2.0, were used to detect anti-TB drug-resistant isolates. STATA 17 was utilized to perform descriptive statistics, bivariate, and multivariate regression analyses. Of 560 PTB-symptomatic participants, 21.8% ((95% confidence interval (95 CI): 18.4–25.2%)) were culture-positive, resulting in a point prevalence of 1,183/100,000 attendees. Amongst HWS attendees, culture-positive TB occurred most commonly in persons 18–33 years of age (28.5% (95 CI 23.4–34.3%)). Other participant characteristics significantly associated with culture-positive PTB were as follows: rural residents (adjusted odds ratio (aOR) 2.65; 95 CI 1.38–5.10), married participants (aOR 2.43; 95 CI 1.28–4.63), family members >5 per household (aOR 1.84; 95 CI 1.04–3.24), and sharing living space (aOR 10.57; 95 CI 3.60–31.13). Also, among 438 participants followed for 12 months after showing negative TB culture results while at the HWS, 6.8% (95 CI 4.4–9.4%) developed or contracted culture-positive TB post-residency at the HWSs. Of the 122 tested isolates, 20 (16.4%) were isoniazid (INH) and/or rifampicin (RIF) resistant. Multidrug-resistant (MDR) TB was detected in 15 cases (12.3%), five of which were fluoroquinolones (FLQs) resistant. The findings from this study should raise a concern about HWSs as potential high-risk settings for TB transmission. It is recommended that appropriate control measures be instituted that include compulsory TB testing and tightened infection control at HWSs, where an increased risk exists for transmission of TB.